Analisis Rekayasa dan Karakterisasi Briket Bahan Bakar dari Limbah Serat Kenaf - Sudarja Sudarja (Universitas Muhammadiyah Yogyakarta, 2009)
The amount of rejected hibiscus cannabinus fiber reaches 30% during harvesting and 10% of the fiber bought by industries because they are not satisfied the quality requirement. In other words, 37% of the harvested hibiscus cannabinus fiber is rejected and become waste. On the other hand, the society need alternative fuel instead of fossil fuel due to its availability and high-price. Therefore, a study on the utilization of hibiscus cannabinus fiber waste for alternative fuel is urgently required. The main materials used in this research are hibiscus cannabinus fiber waste and starch glue. The first step is producing star-coal by burning the hibiscus cannabinus fiber in a closed tube (chamber) followed by producing starcoal briquette by blending starcoal powder and starch glue, and finally, pressing it in a pressing machine. The characteristic being studied are: water content (comply to ASTM-D-3173), calorific value (ASTM D-2015 and ASTM D-5865-03), and ash content (ASTM D-3174). The result of the research shows that the average calorific value of hibiscus cannabinus fiber waste is 6595,65 kal/gram while that of the briquette compacted at 1090 psi or above was 7394,14 kal/gram. The average water content was 10,9%, and ash content is 31,67%. Advanced study concerning the percentage of fly ash and economic aspects was recommended in order to justify its feasibility.